Analysis of microcirculation measurements by novice users trained by a standardized interactive tutorial: An inter-observer variability study - Cerny, Vladimir; Abdo, Islam; George, Ronald B; Maddison, Liivi; Sharawi, Nivin; Lehmann, Christian (Clinical hemorheology and microcirculation, 2016)
Excessive time for analysis may impede microcirculatory studies with large amounts of video data. Engaging more personnel in the analyses seems to be a rational approach in that scenario and could shorten the time-interval between capturing images and obtaining results. Our hypothesis was that novice users would be able to determine standard microcirculatory parameters using a semi-automated software with an acceptable degree of variability after participating in a standardized interactive training session. 14 volunteers were included in the study. All volunteers analyzed separately the same sample video after the training. The kappa statistic was calculated for the primary outcome parameter microvascular flow index (MFI) within small and large vessels and indicated a fair level of agreement in the results of the novice users. A standardized interactive tutorial can be useful to teach microcirculatory analysis in previously untrained subjects.
Keywords: Cardiology; Software; software; kardiologie; audiovizuální záznam; Humans; Video Recording; lidé; mikrocirkulace; Europe; automatizace; Models, Statistical; ústa; Canada; Kanada; Mouth; Automation; statistické modely; odchylka pozorovatele; Observer Variation; Microcirculation; Evropa